2005
DOI: 10.1128/mcb.25.8.3040-3055.2005
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Myogenesis under Hypoxia

Abstract: Previous studies have indicated that myoblasts can differentiate and repair muscle injury after an ischemic insult. However, it is unclear how hypoxia or glucose deprivation in the ischemic microenvironment affects myoblast differentiation. We have found that myogenesis can adapt to hypoxic conditions. This adaptive mechanism is accompanied by initial inhibition of the myoD, E2A, and myogenin genes followed by resumption of their expression in an oxygen-dependent manner. The regulation of myoD transcription by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
171
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(193 citation statements)
references
References 57 publications
21
171
0
Order By: Relevance
“…13 Regenerating muscle produces abundant angiogenic growth factors and induces angiogenesis. Myocyte regeneration occurs only under oxygen supply that is supported by blood perfusion through collaterals, 9 in agreement with our findings. HGF and bFGF potentially promote the growth of skeletal muscle.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…13 Regenerating muscle produces abundant angiogenic growth factors and induces angiogenesis. Myocyte regeneration occurs only under oxygen supply that is supported by blood perfusion through collaterals, 9 in agreement with our findings. HGF and bFGF potentially promote the growth of skeletal muscle.…”
Section: Discussionsupporting
confidence: 82%
“…[9][10][11][12] Acute ischemia induces gradual deterioration of energy metabolism in muscle, followed by cell death or adaptation. Proliferation of satellite cells begins as early as 3 days after the ischemic insult.…”
mentioning
confidence: 99%
“…Ono et al demonstrated HIF-1α accumulated in the nucleus of myogenin-positive myoblasts on day 1 of differentiation, even at normal oxygen concentrations, while the amount of mRNA of the protein was constant 26) , corresponding to our present results. HIF-1α has an essential role in myogenic differentiation, and the regulation of protein expression is independent of oxygen concentration 25,26). HIF-1α protein expression was tightly regulated by HSP90 26) .…”
Section: Discussionmentioning
confidence: 98%
“…The effect of hypoxia on myogenesis is independent of HIF-1α, while myogenesis can also adapt to glucose deprivation 25) . Interestingly, HIF-1α protein is required for C2C12 myogenesis 26) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation